Walked and talked with Mandarin - Yong, Ying Mei (Pusat Bahasa Moden dan Sains Kemanusiaan, 2010)
26 - 28 March 2010. Nothing seems abnormal when using Mandarin at Jonker Walk, Malacca. That was a real life experience learnt by a group of 35 UMP students from UHF2011/2111 Intermediate Mandarin course who had participated in Mandarin Learning Camp 2010 held at Semabok Inn, Malacca.